Synthesis of Catalytic Membrane Surface Composites for Remediating Azo Dyes in Solution - Sutherland, Alexander (My University, 2019)
In the past 30 years zero-valent iron (ZVI) has become an increasingly popular reducing agent technology for remediating environmental contaminants prone to chemical degradation. Azo dyes and chlorinated organic compounds (COCs) are two classes of such contaminants, both of which include toxic compounds with known carcinogenic potential. ZVI has been successfully applied to the surfaces of permeable reactive barriers, as well as grown into nanoscale particles (nZVI) and applied in-situ to chemically reduce these contaminants into more environmentally benign compounds. However, the reactivity of ZVI and nZVI in these technologies is limited by their finite supply of electrons for facilitating chemical reduction, and the tendency of nZVI particles to homo-aggregate in solution and form colloids with reduced surface area to volume ratio, and thus reduced reactivity. The goal of this project was to combine reactive nanoparticle and membrane technologies to create an electro-catalytic permeable reactive barrier that overcomes the weaknesses of nZVI for the enhanced electrochemical filtration of azo dyes in solution. Specifically, nZVI was successfully grown and stabilized in a network of functionalized carbon nanotubes (CNTs) and deposited into an electrically conductive thin film on the surface of a polymeric microfiltration support membrane. Under a cathodic applied voltage, this thin film facilitated the direct reduction of the methyl orange (MO) azo dye in solution, and regenerated nZVI reactivity for enhanced electro-catalytic operation. The electro-catalytic performance of these nZVI-CNT membrane surface composites to remove MO was validated, modelled, and optimized in a batch system, as well as tested in a dead-end continuous flow cell system. In the batch experiments, systems with nZVI and a -2 V applied potential demonstrated synergistic enhancement of MO removal, which indicated the regeneration of nZVI reactivity and allowed for the complete removal of 0.25 mM MO batches within 2-3 hours. Partial least squares regression (PLSR) modelling was used to determine the impact of each experimental parameter in the batch system and provided the means for an optimization leading to maximized MO removal. Finally, tests in a continuous system yielded rates of MO removal 1.6 times greater than those of the batch system in a single pass, and demonstrated ~87% molar removal of MO at fluxes of approximately 422 lmh. The work herein lays the foundation for a promising technology that, if further developed, could be applied to remediate azo dyes and COCs in textile industry effluents and groundwater sites respectively.
Keywords: Catalytic Membranes; Nano Zero-Valent Iron; Carbon Nanotubes; Azo Dyes; Chlorinated Organic Compounds; Methyl Orange; Conductive Membranes; Partial Least Squares Regression